What is Foucault’s Discourse? - Gasmi, Abd El Hak (LANGUAGE ART, 2022)
This research presents the concept of discourse according to the French thinker Michel Foucault and its relationship to the linguistic studies that he was influenced by, in terms of identifying the angles in which his perception of this concept agrees with the linguistic perception, as well as the aspects in which it is distinguished from it. The research is also exposed to the definitions Foucault presented to discourse on several occasions from different sides, trying to avoid any unilateral view in dealing with this concept, by including all its dimensions that Foucault called for. The research started by recalling the general theoretical orientation that preoccupies Foucault, and the characteristics of his theory, and then follows its definitions of the discourse from the aspects through which it reaches it, in terms of being a group of collective utterances then by the structure of it rules that, and finally in terms of being a social practice.